Scaling and Dynamic Resource Reallocation in NFV: Challenges and Research Perspectives - Hoang, Thanh Tung; Pham, Manh Linh; Nguyen, Hoai Son (International Journal of Electrical and Computer Engineering Systems, 2024)
Network Function Virtualization (NFV) has brought incredible experiences for Internet users and network operators. NFV enables the implementation of Virtualized Network Functions (VNFs) as software running in High Volume Servers (HVSs) to execute a Service Function Chain (SFC) to satisfy service demands of Internet users. During the execution of SFCs, VNFs and Virtual Links (VLs) tend to change their resource requirements due to the dynamic nature of the end user’s demands. In this paper, we focus on dynamic resource allocation to the elements of SFC throughout the SFC process to adapt to the elasticity in demand from users by providing an overall picture of NFV and the scaling problem of SFC. We then review and analyze related studies on dynamic resource allocation of NFV systems during SFC operation and analyze the results of these projects. The most recent works are also classified based on several criteria to highlight their approaches, achievements, and also shortcomings. Finally, we introduce some research directions to deal with the scaling problem during SFC operation that needs more attention from researchers to inspire future work in the elastic operation of NFV-enabled systems.